Idioma y territorio en las narrativas del Gran Chaco: el archivo invisible de los matacos - Laura Destéfanis (Cuadernos LIRICO)
The Wichí-Weenhayek people of the Gran Chaco postulate a conception of archive that starts on the work with the oral transmission of the cultural treasure and the forest as an expanded support of communication, knowledge and reservoir. Based on this conceptual reconsideration, which seeks to legitimize and preserve that heritage, the paper analyzes the strategies used by the first two archival fictions that took the Wichí-Weenhayek case from an approach to their own postulates: Eisejuaz (1971), by Sara Gallardo, and En el país del silencio (1987), by Jesús Urzagasti.